2008
DOI: 10.1037/1072-5245.15.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Family conflict and intragroup marginalization as predictors of acculturative stress in Latino college students.

Abstract: This study examined the impact of family conflict and intragroup marginalization on acculturative stress in 188 bicultural Latino college students. Results showed that low parental income, low acculturation, perceived family conflict, and perceived intragroup marginalization were related to higher acculturative stress for participants. Intragroup marginalization accounted for a statistically significant proportion of the variance in acculturative stress after all variables were controlled. The findings emphasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
114
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(124 citation statements)
references
References 12 publications
7
114
0
Order By: Relevance
“…For example, a recent study found increased levels of acculturative stress for bicultural Latino college students who experienced intragroup marginalization (Castillo et al 2008). Furthermore, a study by Benet-Martínez and Haritatos (2005) found that bicultural students who perceived the heritage culture and dominant culture as incompatible were significantly more likely to experience stress, from being perceived by their heritage culture group members as being "too White" or by the dominant group members as "too ethnic."…”
Section: Intragroup Marginalization and Latino College Studentsmentioning
confidence: 96%
See 4 more Smart Citations
“…For example, a recent study found increased levels of acculturative stress for bicultural Latino college students who experienced intragroup marginalization (Castillo et al 2008). Furthermore, a study by Benet-Martínez and Haritatos (2005) found that bicultural students who perceived the heritage culture and dominant culture as incompatible were significantly more likely to experience stress, from being perceived by their heritage culture group members as being "too White" or by the dominant group members as "too ethnic."…”
Section: Intragroup Marginalization and Latino College Studentsmentioning
confidence: 96%
“…described this type of intragroup marginalization as homeostatic pressure, which involves family members pressuring the acculturating individual to not change and requesting the person to maintain traditional heritage culture values and behaviors. Similar to marginalization from peers, intragroup marginalization from family has also been shown to predict family conflict and acculturative stress in Latino college students (Castillo et al 2008).…”
Section: Case Conceptualizationmentioning
confidence: 97%
See 3 more Smart Citations